2014
DOI: 10.1136/bjophthalmol-2014-305495
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile of accelerated corneal cross-linking versus conventional cross-linking: a comparative study on ex vivo-cultured limbal epithelial cells

Abstract: The 30 mW UV-A irradiation used in ACXL appears to be safe on cultured LECs in comparison with 3 mW used in CXL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
0
11
0
3
Order By: Relevance
“…14 Our group has shown that higher intensities of 30 mW/cm 2 UV-A used in ACXL is safe on cultured LECs. 15 In our study, all groups showed variability in disease progression, and varying improvement in tomographic data when compared within and between groups. Improvement in the mean CDVA and SE was seen in all groups at 1-year follow-up period.…”
Section: Discussionmentioning
confidence: 90%
“…14 Our group has shown that higher intensities of 30 mW/cm 2 UV-A used in ACXL is safe on cultured LECs. 15 In our study, all groups showed variability in disease progression, and varying improvement in tomographic data when compared within and between groups. Improvement in the mean CDVA and SE was seen in all groups at 1-year follow-up period.…”
Section: Discussionmentioning
confidence: 90%
“…Total RNA was extracted using TRIzol reagent (Ambion, Carlsbad, CA, USA) and converted to cDNA from cultured cells as described previously. 26 Briefly, equal amounts of extracted RNA were converted to cDNA using High-Capacity cDNA Reverse Transcriptase Kit (Life Technologies, Carlsbad, CA, USA) according to the manufacturer's instructions and stored at À208C. Reverse transcriptase-PCR was performed on an Applied Biosystems Veriti (Life Technologies, Foster City, CA, USA) with rpe65 and gapdh gene-specific primers ( Table 1).…”
Section: Reverse Transcriptase Polymerase Chain Reaction (Rt-pcr) Formentioning
confidence: 99%
“…The PCR was set in a total volume of 25 lL as described previously. 26 The products were resolved on 1.5% agarose gel and documented on a UV transilluminator (Vilber Lourmat, Mumbai, India).…”
Section: Reverse Transcriptase Polymerase Chain Reaction (Rt-pcr) Formentioning
confidence: 99%
“…In another ex vivo study, 27 an increase in cell apoptosis in limbal epithelial cell cultures with both UVA of 3 and 9 mW/cm 2 irradiation was observed. The absence of in vivo limbal cell damage in the former study could be attributed to the presence of a protective layer of tear film and the limbal stem cells located in a deep layer.…”
Section: Discussionmentioning
confidence: 91%